PENERAPAN THERAPEUTIC ARCHITECTURE TERHADAP PERANCANGAN GERIATRIC CLUB HOUSE - Michael Ricardo; Nafiah Solikhah (Jurusan Arsitektur dan Perencanaan, 2023)
The phenomenon for the design of the geriatric association house associated with statistical data on the growth of elderly people in Indonesia, to be precise in the city of Jakarta. The number reaches 9.2% of the total population and exceeds the national average of only 7%. Then, the lack of social space needs facilities to improve the quality of life of the elderly at the end of their lives. Facilities supporting these needs must be able to accommodate and pay attention to the standard needs and special needs of the activities of the elderly. The method used is the process of applying an object approach designed with a literature study and precedent study approach. The design of the social facility